Glutamine and exercise - Mioko Nagashima; Yuji Soejima; Kazuto Saito (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Glutamine is the most abundant free amino acid in the human body. It is important in gluconeogenesis, a precursor for nucleotide synthesis, and the antioxidant function of glutathione (GSH), and is a fuel for immune cells and enterocytes. The plasma concentration of glutamine is decreased in patients with trauma, sepsis and athletes with overtraining. Plasma glutamine increases after short-term exercise and balanced training; however it decreases after prolonged exhaustive exercise and overtraining. When comparing the plasma glutamine in athletes of different types of sports, cyclists have higher concentrations than all other sports. Glutamine intake increases GSH, which is important for scavenging reactive oxygen species (ROS) during exercise. The data presented in this short review indicate that glutamine administration may increase GSH, resulting in upregulated antioxidant activities, and reduce exercise-induced apoptosis of lymphocyte and neutrophil, and muscle damage.